Factors associated with tobacco use among the adult population in sarawak, malaysia:a cross sectional study - Md Mizanur, Rahman; Mohd Taha, Arif; Mohd Fadzillah, Abd Razak; Mohd Raili, bin Suhaili; Zainab, Tambi; Cliffton, Akoi; Eunice, Melissa; Hasienti, Hussein (Universiti Malaysia Sarawak, 2014)
Background: Consumption of tobacco in any form is one of the leading causes of preventable mortality. The World Health Organization recommends that it should be monitored regularly. A study was conducted to estimate the prevalence of tobacco use and factors associated with it among rural adult population in Sarawak. Methods: This was a cross-sectional study conducted among the adult population. Data were collected from ten Kampungs (villages) in Kota Samarahan and Kuching Division by face-to-face interview using modified Global Adult Tobacco Survey (GA TS) questionnaire. Non-probability sampling method was adopted to select the villages. All the households of the selected villages were visited and an adult member, irrespective of sex, was selected randomly from each household. The study was conducted for a period of one year from July 2012 to June 2013. After missing value imputation, 1000 data were analysed using statistical software SPSS 19.0 version. Results: Analysis showed that 30.9% of the respondents were current tobacco users and 11% were past tobacco users. The mean age (SD) of starting tobacco use was 18.1 (6.48) years. The mean frequency of tobacco use was 14 times per day. Hierarchical Logistic regression analysis revealed that age with male sex (OR=1.064, 95% CI: 1.052, 1.076), secondary education (OR=-2.712; 95% CI: 1.122, 6.555), higher secondary and above (OR=3. 571; 95% CI: 1.641,7.774), business as occupation (OR =3.152; 95% CI: 1.732, 5.735) environmental exposure such as smoking at working place (OR=2.754;95% CI: 1.895,4.002), coffee house (OR=2. 274;95% CI: 1.32,3.919) and at home (OR=1. 827;95% CI: 1.242,2.687) appeared to be important predictors of tobacco use (p<0.05). ConclusionS: A large proportion of males used tobacco products. Though tobacco use was negligible among females, nonetheless they would be potential users. Environmental exposure to tobacco appeared to be important predictors. Tobacco control campaigns should target banning of tobacco use in more closed and open areas and also to intensify the monitoring of all forms of tobacco used by the population